O uso de fitoterápicos no tratamento da fibromialgia: uma revisão de escopo - Silva, Alane Freire da (2023)
Introduction: Fibromyalgia (FM) is a non-inflammatory condition characterized by chronic and widespread pain in the musculoskeletal system, with possible implications in other systems. Individuals with fibromyalgia often rely on medication for pain relief. Recently, Herbal Medicine has gained more prominence in the therapeutic approach for these patients; however, few studies have examined the efficacy of herbal remedies for treating this syndrome. Objective: This study aimed to conduct a scientific review on all herbal remedies used in the treatment of fibromyalgia. Method: A scoping review was conducted from March to November 2023. Primary and secondary research, quantitative, qualitative, and mixed-methods studies from the year 2000 onwards, involving humans or animals and any language, were considered eligible. Results: Pain, anxiety, fatigue, and oxidative stress were the focus of most studies. Herbal remedies such as Panax ginseng, Nigella sativa, Eplingiella fruticosa, Ginkgo biloba, Ginger powder (Zingiber officinale), Ocimum basilicum, Annona muricata, Cannabis, Saffron (Crocus sativus), and Willow bark (Salix alba) were identified as potential treatments for fibromyalgia. Conclusion: Different plants and substances have shown promising results in treating symptoms of anxiety and muscle pain associated with fibromyalgia. This may provide safe and effective alternatives for treating these conditions.